2009
DOI: 10.1021/la803179q
|View full text |Cite
|
Sign up to set email alerts
|

SAMs on Gold Derived from the Direct Adsorption of Alkanethioacetates Are Inferior to Those Derived from the Direct Adsorption of Alkanethiols

Abstract: Self-assembled monolayers (SAMs) on gold derived from the direct adsorption of thioacetic acid S-decyl ester (C10SAc) and thioacetic acid S-octadecyl ester (C18SAc) were compared to the corresponding SAMs derived from the analogous adsorption n-decanethiol (C10SH) and n-octadecanethiol (C18SH). All SAMs were characterized using ellipsometry, contact angle goniometry, polarization modulation infrared reflection absorption spectroscopy (PM-IRRAS), and X-ray photoelectron spectroscopy (XPS). The comparison reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 67 publications
6
95
0
Order By: Relevance
“…Our computed dissociation transitions state and energetic are in good agreement with earlier experimental observations [88,91,92]. Our calculations seem therefore to suggest a homolytic cleavage assisted by a polarized transition state.…”
Section: Thioacetatessupporting
confidence: 90%
See 2 more Smart Citations
“…Our computed dissociation transitions state and energetic are in good agreement with earlier experimental observations [88,91,92]. Our calculations seem therefore to suggest a homolytic cleavage assisted by a polarized transition state.…”
Section: Thioacetatessupporting
confidence: 90%
“…Moreover, it has been shown that experimentally the thioacetates undergo spontaneous deprotection upon adsorption, leading to radical thiols to be adsorbed on the surface [91,92]. This approach has been successively used for the synthesis of SAMs of different nature [92].…”
Section: Thioacetatesmentioning
confidence: 99%
See 1 more Smart Citation
“…1(e)] hence, an imperfect molecular self-assembly will still work¯ne and will provide a functional TJMD. 35 In a TJMD, molecular channels are chemically anchored between the two metal electrodes [ Fig. 1(e)].…”
Section: Molecules Serve As a Device Element Not As A Physical Barriermentioning
confidence: 99%
“…8,9,[13][14][15] It has been observed that the direct adsorption of alkanethioacetates (ATAs) on gold in solution generates loosely packed and disordered SAMs compared to the corresponding alkanethiols (ATs). 8,13,15 A kinetics study showed that the adsorption rate is slower for ATAs in pure solvents than for ATs. 14 Fully covered monolayers from aromatic thioacetates were formed after a longer immersion period of several days or in a concentrated 30 mM solution.…”
mentioning
confidence: 99%